2020
DOI: 10.1111/1750-3841.15373
|View full text |Cite
|
Sign up to set email alerts
|

The hypoglycemic effect of extract/fractions from Fuzhuan Brick‐Tea in streptozotocin‐induced diabetic mice and their active components characterized by LC‐QTOF‐MS/MS

Abstract: Fuzhuan Brick‐Tea is a postfermented product with the hypoglycemic effect, which is prepared from the leaves of Camellia sinensis var. sinensis. However, the material basis associated with the hypoglycemic effect was not clear. The present research was designed to explore the hypoglycemic effect of extract/fractions from Fuzhuan Brick‐Tea in streptozotocin‐induced type II diabetic mice. Then an ultra‐high pressure liquid chromatography along with quadrupole time of flight mass spectrometry was used to analyze … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…Green tea consumption (2 g/kg) reduced 14•3 % of blood glucose in 21 d of diabetic rats (13) . After being intragastrically administered with 100 mg/kg of Fuzhuan Brick-Tea extract for 4 weeks, 33 % of the serum glucose levels of diabetic mice were reduced (14) . This means that 5-fold lower dose of DTPE achieved similar result to F. cretica extract; 2-fold lower dose of DTPE achieved 2-fold higher glucose-lowering effect than S. brevistigma extract;…”
Section: Discussionmentioning
confidence: 99%
“…Green tea consumption (2 g/kg) reduced 14•3 % of blood glucose in 21 d of diabetic rats (13) . After being intragastrically administered with 100 mg/kg of Fuzhuan Brick-Tea extract for 4 weeks, 33 % of the serum glucose levels of diabetic mice were reduced (14) . This means that 5-fold lower dose of DTPE achieved similar result to F. cretica extract; 2-fold lower dose of DTPE achieved 2-fold higher glucose-lowering effect than S. brevistigma extract;…”
Section: Discussionmentioning
confidence: 99%
“…101 The novel theophylline derivatives in Fuzhuan tea may help to ameliorate the disorder of glucolipid metabolism, which protects pancreatic β-cells from oxidative damage, promotes insulin secretion, increases insulin sensitivity in peripheral tissues, and decreases glucose absorption. 120 Tea polyphenols, TPS, and caffeine in black tea and green tea can effectively reduce the absorption of fatty acids, improve serum and liver lipid levels, reduce serum triglyceride levels, and regulate the expression of IL-6 and TNF-α gene. 121,122 Notably, TPS and tea polyphenols showed the ability to reduce serum leptin levels and exert anti-inflammatory activity synergistically, indicating that different tea active ingredients have the potential of synergistic antidiabetic effects.…”
Section: Inhibition Of Ptp1b and Othermentioning
confidence: 99%
“…Given that it is considered a folk drink that can cleanse the palate, it is popular among ethnic groups in the southern and western border regions of China, which lack vegetable and fruit cultivations [1]. With the development of modern medicine, recent studies have shown that FBT demonstrates significant pharmacological activity in the regulation of blood lipids and blood glucose [2–5], as well as anti‐inflammatory and antioxidant activities [6–8]. Therefore, FBT is currently attracting the attention of consumers and researchers as a health product.…”
Section: Introductionmentioning
confidence: 99%